ACTIVATED CARBON OF GELAM WOOD LOWERS THE METAL CONTENT OF PAPUYU FISH IN THE ALALAK RIVER - Tuti Alawiyah; Ika Avrilina Haryono; Rahmadani (JURNAL KATALISATOR, 2023)
Alalak River is a river that has high industrial activity, so that the lead metal content due to industry in this Alalak river is very high, which is 0.405 mg/Kg in papuyu fish that live in the river. There needs to be an effort in reducing metals, one of which is with compounds that have adsorption properties such as gelam wood plants. Gelam wood is a plant that is widely found, especially in the South Kalimantan area, this wood has a cellulose value of 76.8% and the ability to absorb iodine of 791.59 mg/g. The purpose of this study was to test the characteristics of the ability of gelam wood activated carbon in reducing lead (pb) levels in papuyu fish in the Barito river and see the effect of time variance in reducing lead (pb) levels. This research method is a true experiment to determine the effect of lead (pb) reduction activity in different exposure times. This study used a control group and a test group with exposure in several variations of contact time with gelam wood activated carbon.The results showed that the characteristics of gelam wood activated carbon were in accordance with the provisions of the Indonesian National Standard (SNI). While the significance value of the decrease in lead (pb) levels with exposure to activated carbon in gelam wood is <0.05 so it can be concluded that there is a significant effect on the decrease in pb levels.